Implementasi Program Rumah Pintar dalam Meningkatkan Keterampilan Literasi dan Numerasi Dasar Siswa SD - Damayanti, Amelia Eka; Nurrochma, Novenntya Putri Prastiwi; Khansa, Nur Aqila; Persada, Yuris Indria; Wulandari, Septi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to address the challenges of low reading, writing, and arithmetic (literacy and numeracy) skills at SDN 1 Surodakan elementary school, especially in rural areas. The community service activity was carried out at SDN 1 Surodakan, Trenggalek Regency, by describing the implementation of the